Next-Generation Precision Healthcare: AI-Driven Clinical Intelligence, Predictive Analytics, and Adaptive Decision Support Systems (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2025)
The healthcare sector is increasingly generating vast amounts of data—structured and unstructured, clinical and nonclinical—requiring systematic organization for practical use. Machine learning and statistical modeling have demonstrated predictions with accuracy superior to conventional risk models. However, model implementations have focused on a one-off task rather than incorporation into clinical workflows. For successful utilization, predictive models need to be embedded in a connected data ecosystem and continually refreshed—refreshed by new data available within the clinical setting itself, as well as new knowledge derived from the scientific community. Adaptative decision support evaluates patients against a set of clinical guidelines that enables deviations tailored to individual context, integrates with electronic health record (EHR) systems, operates in real time or batch mode, and has an architecture that supports transparency and an understanding of inference mechanisms—by clinicians as well as patients. Analytical engines are biased toward interpretable models, but the choice is ultimately determined by the clinician. Improving the accuracy and reducing errors of a tool designed to enhance decision-making should clearly be a priority.
Keywords: Precision Healthcare; Artificial Intelligence in Medicine; Clinical Decision Support Systems (CDSS); Predictive Healthcare Analytics; AI-Driven Clinical Intelligence; Personalized Patient Care; Adaptive Decision Support; Machine Learning for Healthcare; Digital Health Innovation; Data-Driven Clinical Outcomes